(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Malaria poses a significant global public health challenge as an infectious disease transmitted by vectors, particularly affecting young children, with substantial morbidity and mortality rates. This study formulates criteria ensuring the stability, uniqueness, and existence of a fractional-order malaria-malnutrition framework utilizing the Caputo-Fabrizio differential operator, employing the fixed-point methodology. The adoption of this fractional differentiation technique is an innovative approach within such biological contexts. Furthermore, we obtain the earliest approximate solutions for the formulated model through the iterative Laplace transform procedure. At last, numerical simulations are performed. using the selected model parameter values. Our findings indicate that ensuring a well-rounded diet is crucial for mitigating the spread of malaria among young children, thereby reducing both morbidity and mortality.